The development of a multimedia application in learning Japanese: a step forward in Malaysia’s look east policy / Naginder Kaur, Nor Arzami Othman and Hana Wahida Adli - Kaur, Naginder; Othman, Nor Arzami; Adli, Hana Wahida (Universiti Teknologi MARA, 2020)
The Look East Policy Programme in Malaysia, that was rejuvenated recently by Tun Dr Mahathir Mohamad, the seventh Prime Minister of Malaysia, focuses on a few key areas, namely, education, training and investment, consequently, making the learning of Japanese as a third language fundamental for Malaysian undergraduates as a key point to set them apart from others, especially in multicultural or intercultural competency atmospheres. On the global sphere, the emergence of Japan as a rising force in industrialisation has also made the learning of Japanese essential for non-native speakers. Hence, it has become relevant and necessary to pay more attention to the learning of the Japanese language in all corners of the globe. However, for many, it is a daunting task, mainly because of unfamiliarity with the Japanese script and the vast number of characters in the language. This paper outlines an initiative taken by the researchers in developing and testing a multimedia application for Japanese language learning using sensory learning and Tangible User Interface, adopting the five-step ADDIE model. The paper maps out the detailed step-by-step process in developing this application, named ATAMJHS for the learning of the Hiragana syllabary, using Malay language mnemonics as the learning guide, thus, making it a truly novel application for use by any Malayliterate learner in South East Asia and anywhere beyond, ensuring a more rewarding and sustainable partnership with Japan in the future, through quality education (SDG 2030: Goal 4), specifically in upholding and realising the Look East Policy in the Malaysian context.